The real planet of the apes a new story of human origins - Begun, David R. (Princeton University Press, 2016)
"Was Darwin wrong when he traced our origins to Africa? The Real Planet of the Apes makes the explosive claim that it was in Europe, not Africa, where apes evolved the most important hallmarks of our human lineage--such as dexterous hands and larger brains. In this compelling and accessible book, David Begun, one of the world's leading paleoanthropologists, transports readers to an epoch in the remote past when the Earth was home to many migratory populations of ape species. Drawing on the latest astonishing discoveries in the fossil record as well as his own experiences conducting field expeditions across Europe and Asia, Begun provides a sweeping evolutionary history of great apes and humans. He tells the story of how one of the earliest members of our evolutionary group--a new kind of primate called Proconsul--evolved from lemur-like monkeys in the primeval forests of Africa. Begun vividly describes how, over the next ten million years, these hominoids expanded into Europe and Asia and evolved climbing and hanging adaptations, longer maturation times, and larger brains, setting the stage for the emergence of humans."-- Dust jacket.